Improving Students’ Communication Skills of Phitaksad Vitayya Mulniti School, Kampung Yarang, Pattani Thailand - Fadila, Lisa; Pazira, Nurul; Abdul Mugni; Jasafat, Jasafat; Zakariya, Helmee Haji (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
Lack of courage and confidence to speak can have a significant negative impact. Communication skills are one of the important elements that must be possessed by every individual today, this is because as the times and the world of education develop, improving students' communication skills has an important role in preparing them to face future challenges. Therefore, to overcome this, one of the steps that can be taken is to improve students' communication skills so that they can have the confidence and courage to speak in front of the class or in public, and improve their ability to provide and disseminate information, ideas, and thoughts. The goal of improving Communication Skills is carried out in the framework of the International Community Service Activity program in collaboration between the Institut Agama Islam Negeri (IAIN) Lhokseumawe and Ar-raniry State Islamic University (UIN Ar-raniry) Banda Aceh. This activity was carried out in one of the schools and boarding schools in the city of Pattani, Thailand.